Adenomyosis a Rare Contributor to Severe Primary Post-Partum Haemorrhage - Olumodeji, Ayokunle Moses; Aborisade, Oluwabusayo Abayomi; Adefemi, Ayodeji Kayode; Adedeji, Modupe Olatokunbo; Olumodeji, Ufuoma Oluwaseyi (International Journal of Innovative Research in Medical Science, 2021)
Adenomyosis is a challenging clinical condition for women of reproductive age with both proven and speculated, major gynaecologic and obstetric consequences. We present the case of a woman who had adenomyosis of the uterus, a successful in-vitro fertilized (IVF) conceived twin pregnancy, and severe primary postpartum haemorrhage (PPH) during caesarean section. The 38-year-old, gravida 2, para 0+1, with a 6-year history of prior infertility, had severe primary postpartum haemorrhage at caesarean delivery of a live set of twins at estimated gestational age of 35weeks. Conservative treatment included uterine compression and massage, blood transfusion, administration of intravenous carbetocin and application of multiple figure of eight haemostatic sutures at the placenta bed. Intra-operative finding on gross inspection of the uterus was in keeping with focal adenomyosis in the region of the placenta bed. Biopsy of the involved myometrial wall was avoided due to risk of provoking further severe haemorrhage. Her prior medical record revealed pelvic endometriosis at diagnostic laparoscopy prior to conception while being evaluated for infertility. Women with prior infertility and/or endometriosis, due to very probable co-existing adenomyosis, are at high risk of life-threatening, severe post-partum haemorrhage at delivery.